Semiquantitative determination of chromium content of river bed soil of Buriganga River at different locations (Journal of Bangladesh Academy of Sciences, 2011)
Using the technique of Laser Induced Breakdown Spectroscopy, the chromium content of river bed sediment of the Buriganga River is determined at various locations. Hazardous element, chromium is found in addition to other elements such as calcium, magnesium, titanium, sodium etc. The source of this chromium is most likely to be the effluent discharge from the tanneries located nearby. Semi quantitative analyses showed the relative abundances of Cr, Mg, and Ca in the river bed sediment at Kamrangir Char and Shoari Ghat locations are in the ratios of 1:9:23 and 1:11:17, respectively. Key words: Chromium content; River bed soil; Buriganga river DOI: 10.3329/jbas.v34i2.6856Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 123-131, 2010